Crown Dynamics of Several Tree Species in a Tropical Rain Forest - Osada, Noriyuki (1998)
The study was conducted in Pasoh Forest Reserve, Negeri Sembilan. By considering trees as a metapopulation of modules, leaf phenology and crown dynamics were analyzed, specifically in relation to the complexity of their stratification that characterizes the tropical rain forests. The results of leaf phenology study clearly demonstrated that the number of trees flushed was synchronized with the seasonality of rainfall. As a result, two flushing season existed in a year. However, flowering season was restricted to first heavy rainfall season from March to April. Shoot elongated intermittently in most species and only two species showed the continuous growth type. Leaf flushing and falling were synchronized in most of the species. Crown dynamics were analyzed from the change in leaf number inside the crown. Most of small species (less than 15 m tall) expanded their crowns even though they were strongly suppressed. Because canopy around the tower systems was closed and light condition of understory was limited, only shade-tolerant species could regenerate. On the contrary, crown dynamics of middle-height species (from 15 m to 30 m tall) differed according to their light availability. Two canopy trees (larger than 30 m) maintained their crowns without increasing leaf number in the upper parts with high leaf turnover rate. The minimum leaf longevity was 7.9 months in one canopy tree. Smaller trees had the smaller leaf turnover ratio. This is consistent with the reported results of previous research.